A comparative study of bacterial and fungal‐bacterial steady‐state stages of a biofilter in gaseous toluene removal: performance and microbial community. Issue 11 (22nd May 2017) - Zhai, Jian; Shi, Peng; Wang, Zhu; Jiang, Haitao; Long, Chao
Abstract: BACKGROUND: Traditional biofilters can lack efficiency in removing hydrophobic volatile organic compounds (VOCs) due to their low gas‐to‐liquid phase transfer rates. The aim of this research was to construct a high‐performance biofilter for toluene removal, compare the degradation performance with that of a traditional biofilter and reveal the relationship between the microbial community and operational performance with different operational parameters. RESULTS: The results illustrate that compared with conventional biofilters, the removal efficiency (RE) and the maximum elimination capacity (ECmax ) of the high‐performance, fungal and bacterial biofilter (F&B‐BF) increased by 19.6% and 18 g toluene m ‐3 h ‐1, respectively. The bed pressure drop (ΔP/H) decreased by 1.6 cm H2 O m ‐1 at an empty bed residence time (EBRT) of 45 s at pH 4.0 and using nitrate (NO3 ‐ ) as a nitrogen source. CONCLUSION: Low pH values could properly inhibit bacterial growth and progressively allow fungi to predominate in the biofilm. The degrading capabilities of fungi and bacteria were coupled to improve the biofilter performance in toluene removal. Using NO3 ‐ as the nitrogen source could control the biofilms' overgrowth and reduce the ΔP/H value. The experimental data analysis showed that the fungal genus Phialophora and the bacterial genus Alicyclobacillus played key roles in toluene and phenol degradation, respectively. © 2017 Society of Chemical Industry